Perception of land rights, village industrial development, and household entrepreneurial behavior—evidence from non-farm entrepreneurship in rural China - Weng, Yiqing; Wang, Shuifu (Frontiers in Sustainable Food Systems, 2025)
IntroductionHousehold entrepreneurship has a positive significance in increasing farmers’ income, but currently farmers’ entrepreneurial willingness is insufficient and entrepreneurial behavior needs to be further activated. Existing studies have examined the mechanism of entrepreneurial behavior more in terms of individual factors. However, behavioral decisions are the result of internal and external factors. Therefore, we analysed the mechanisms influencing farmers’ entrepreneurial behavior from two aspects: farmers’ internal psychological perception of the stability of land rights and the driving role of village-level industrial development.MethodsOur analysis is based on data from a sample of 2356 farmers in Jiangsu Province, China, and uses mathematical modeling and binary logic modeling methods.ResultsThe results show that the regression coefficient for the perception of land rights on farmers’ entrepreneurial behavior is 0.573; the regression coefficient for village industrial development on farmers’ entrepreneurial behavior is 1.480; and the regression coefficient for the interaction term between perception of land rights and village industrial development on farmers’ entrepreneurial behavior is 0.361. This indicates that both the perception of land rights and village industrial development have a promoting effect on farmers’ entrepreneurial behavior, and village industrial development moderates the impact of perception of land rights on farmers’ entrepreneurial behavior.DiscussionBased on the results of the study, the following implications have been drawn: first, it is necessary to strengthen land rights, regulate and guide the transfer of land, and strengthen the concept of stability of land rights; second, it is necessary to develop local speciality industries, and to help farmers’ employment and entrepreneurship in a variety of forms and through a variety of channels.